Odpowiedź :
x+5y=-9,5 ====> x=-9,5-5y
6(-9,5-5y)-3y=9
-57-30y-3y=9
-33y=66
y=-2
x-10=-9,5
x=0,5
6(-9,5-5y)-3y=9
-57-30y-3y=9
-33y=66
y=-2
x-10=-9,5
x=0,5
6x-3y=9
x+5y=-9,5
6x-3y=9
x=-9,5-5y
6*(-9,5-5y)=9
x=-9,5-5y
57-30y=9
-30y=48
y=-1,6
6x-3y=9
6x-4,8=9
6x=13,8
x=2,3
x+5y=-9,5
6x-3y=9
x=-9,5-5y
6*(-9,5-5y)=9
x=-9,5-5y
57-30y=9
-30y=48
y=-1,6
6x-3y=9
6x-4,8=9
6x=13,8
x=2,3
6x-3y=9
x+5y=-9,5--> x =-9,5-5y
6(-9,5-5y)-3y=9
-57-30y-3y=9
-30y-3y=9+57
-33y=66|:(-33)
y=-2
x=-9,5-5(-2)
x=-9,5+10
x=0,5
y=-2
x=0,5
x+5y=-9,5--> x =-9,5-5y
6(-9,5-5y)-3y=9
-57-30y-3y=9
-30y-3y=9+57
-33y=66|:(-33)
y=-2
x=-9,5-5(-2)
x=-9,5+10
x=0,5
y=-2
x=0,5